2017
DOI: 10.1111/febs.14348
|View full text |Cite
|
Sign up to set email alerts
|

Protection of macrophages from intracellular pathogens by miR‐182‐5p mimic—a gene expression meta‐analysis approach

Abstract: The goals of this study were to (a) define which host genes are of particular importance during the interactions between macrophages and intracellular pathogens, and (b) use this knowledge to gain fresh, experimental understanding of how macrophage activities may be manipulated during host defense. We designed an in silico method for meta-analysis of microarray gene expression data, and used this to combine data from 16 different studies of cells in the monocyte–macrophage lineage infected with seven different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…Macrophage genes associated with the response to intracellular pathogens were identified from three sources. We reanalysed publicly available microarray datasets, essentially as described elsewhere [32] to identify genes that were repeatedly regulated in different studies using a variety of macrophage types and intracellular pathogens. Other genes were obtained from previous RNAi or yeast two hybrid studies [33][34][35][36][37].…”
Section: Thp1 Library Screenmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophage genes associated with the response to intracellular pathogens were identified from three sources. We reanalysed publicly available microarray datasets, essentially as described elsewhere [32] to identify genes that were repeatedly regulated in different studies using a variety of macrophage types and intracellular pathogens. Other genes were obtained from previous RNAi or yeast two hybrid studies [33][34][35][36][37].…”
Section: Thp1 Library Screenmentioning
confidence: 99%
“…Infections with endospores of Bacillus anthracis ANR-1 were performed essentially as described elsewhere [32].…”
Section: Am-mdm Transfection and Infectionmentioning
confidence: 99%
“…In addition to regulating cytokine/chemokine production in macrophages, miR-183C also regulates the phagocytosis function of macrophages. A bioinformatics analysis approach revealed that the predicted target sites of miR-182 were over-presented in a set of macrophage intracellular pathogen response (macIPR) genes ( 74 ). Further, Gregory et al.…”
Section: Expression and Function Of Mir-183c In Immune Cellsmentioning
confidence: 99%
“…HMPV infection alters the expression of multiple cellular miRNAs in several cells [ 21 ]. We reported that HMPV upregulated significantly the expression of miR-182–5p, and miR-4634 in moDCs, where we highlighted the upregulation of miR-182–5p [ 15 ], which might contribute to the imbalance of Th17 cells [ 44 ] as shown in unrelated models where miR-182–5p triggers the secretion of cytokines related to a Th2-like profile, leading to high recruitment of neutrophils in the lung and secretion of cytokines such as IL-13 and IL-5 [ 16 ], and protects against different intracellular pathogens, increasing the expression of interferons and other proinflammatory cytokines [ 45 , 46 ]. In A549 cells, the miRNAs expression pattern is different.…”
Section: Mirnas and Their Role In Respiratory Viral Infection Immunitymentioning
confidence: 99%